Software technologies : 11th International Joint Conference, ICSOFT 2016, Lisbon, Portugal, July 24-26, 2016, Revised selected papers /: 11th International Joint Conference, ICSOFT 2016, Lisbon, Portugal, July 24-26, 2016, Revised selected papers. (2017) - Unknown
No abstract available